Sleep-Related Problems in Night Shift Nurses: Towards an Individualized Interventional Practice - Alfonsi, Valentina; Scarpelli, Serena; Gorgoni, Maurizio; Pazzaglia, Mariella; Giannini, Anna Maria; De Gennaro, Luigi (Frontiers in Human Neuroscience, 2021)
Rotating shifts (mostly 8- or 12-hours) are common among nurses to ensure continuity of care. This scheduling system encompasses a number of adverse health and performance consequences. One of the most injurious effects of night-time shift work is the deterioration of sleep patterns due to both circadian rhythm disruption and increased sleep homeostatic pressure. Sleep problems lead to secondary effects on other aspects of wellbeing and cognitive functioning, increasing the risk of errors and workplace accidents. A wide range of interventions have been proposed to improve sleep quality of nurses and promote an increase in attention levels. In recent years, particular attention has been paid to individual and environmental factors mediating the subjective ability to cope with sleep deprivation during the night shift. Given the predictive role of these factors on negative impact of night shift, an individualized intervention could represent an effective countermeasure by ensuring suitable management of shift schedules. Therefore, the aims of this mini-review are to (a) provide an updated overview of the literature on sleep problems in night shift nurses and their adverse consequences and (b) critically analyze the psychosocial factors that mediate the negative impact of shift work with the ultimate goal of defining an effective countermeasure based on an individualized approach.